Peran BPJS Ketenagakerjaan Kota Tanjungpinang Terhadap Jaminan Sosial Tenaga Kerja Di Kota Tanjungpinang - Aditya Wahyu Saputra; Panji Al Falah; Mellyana Candra (Lembaga Pengembangan Kinerja Dosen, 2024)
BPJS (Social Security Administering Agency) in Law No. 24 of 2011 is a legal entity established to administer social security programs. BPJS aims to realize the provision of guarantees for the fulfillment of the basic needs of a decent life for each participant and/or their family members. The purpose of this research is to find out the role of BPJS Employment in Tanjungpinang City and analyze the influence of the role of BPJS Employment on the workforce, whether it is in accordance with the objectives of BPJS Employment. The method used by the author in this research is literature study, namely data collection techniques by reading, writing and analyzing the data obtained. In this research, it was found that the important role of Tanjungpinang City BPJS Employment was in carrying out programs from the center which were then further developed. Such as the work accident insurance program (JKK) which was developed into a work accident service center (PLKK) in collaboration with the Navy Hospital.